1992
DOI: 10.1056/nejm199201233260404
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Tuberculosis with Accelerated Progression among Persons Infected with the Human Immunodeficiency Virus

Abstract: Newly acquired tuberculous infection in HIV-infected patients can spread readily and progress rapidly to active disease. There should be heightened surveillance for tuberculosis in facilities where HIV-infected persons live, and investigation of contacts must be undertaken promptly and be focused more broadly than is usual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
363
1
14

Year Published

1994
1994
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 903 publications
(386 citation statements)
references
References 8 publications
8
363
1
14
Order By: Relevance
“…Therefore, in cases of pneumonia, tuberculosis must be considered, especially in regions where the disease is more prevalent and in individuals infected with HIV. (26,27) In southern Brazil, Whites outnumber non-Whites. (28) However, in the present study, 28 (47.5%) of the cases of tuberculous pneumonia occurred in Black individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in cases of pneumonia, tuberculosis must be considered, especially in regions where the disease is more prevalent and in individuals infected with HIV. (26,27) In southern Brazil, Whites outnumber non-Whites. (28) However, in the present study, 28 (47.5%) of the cases of tuberculous pneumonia occurred in Black individuals.…”
Section: Discussionmentioning
confidence: 99%
“…DNA fingerprinting can determine that in many of these outbreaks, the susceptibility of HIV-positive patients to tuberculosis infections and the accelerated breakdown to disease often result in more rapid transmission of the infection [42,50,55,149,153,165]. Furthermore, the study of MTB isolates obtained from AIDS patients by fingerprinting showed that reinfection and relapse both occur in HIV-infected patients, as the susceptibility to superinfections will most likely be related to the immune status of the patient.…”
Section: Use Of Genotyping To Study the Impact Of Hiv/aids And Drug Rmentioning
confidence: 99%
“…In addition to the above studies, molecular epidemiology studies have demonstrated the explosive potential for tuberculosis to progress to disease and spread amongst HIV-infected persons (50). In one study, epidemiological surveillance in a tuberculosis control program detected twelve cases of tuberculosis in a residential facility for persons with HIV disease.…”
Section: The Impact Of Hiv On Tuberculosismentioning
confidence: 99%